The democratic role of campaign journalism: partisan representation and public participation - Birks, Jen (Taylor and Francis, 2010)
Campaign journalism is a distinctive but under-researched form of editorialised news reporting that aims to influence politicians rather than inform voters. In this it diverges from liberal norms of social responsibility, but instead campaigning newspapers make claims to represent the interests or opinions of publics such as their readers or groups affected by the issue. This could be understood as democratically valid in relation to alternative models such as participatory or corporatist democracy. This essay examines journalists’ understanding of the identity and views of these publics, and how their professional norms are operationalised in their journalistic practice in relation to five case studies in the Scottish press. The campaigns are analysed in terms of four normative criteria associated with corporatist and participatory democracy: firstly, the extent to which subjective advocacy is combined with objectivity and accuracy; secondly, the extent to which civic society organisations are accorded access; thirdly, whether the disadvantage of resource-poor groups in society is compensated for; and finally, to what extent the mobilisation of public support for the campaigns aims to encourage an active citizenry.